Dissolved air (pressure) flotation - Bratby, John Raymond (Department of Civil Engineering, 2023)
It appears that, in the past, little attempt has been made to establish the basic parameters influencing the flotation process, or their inter-relationships, on a quantitative basis for the purpose of developing rational design procedures. This thesis investigates those parameters influencing solids removal and thickening by dissolved-air (pressure) flotation and the criteria pertaining to the design of flotation tanks for solids removal and thickening. A review of pertinent literature on flotation is presented. The historical development of flotation is given together with the theory of bubble-particle adhesion. Four common methods of flotation are compared and their inherent advantages and disadvantages are discussed. Dissolved-air (pressure) flotation, the method used in this investigation, is considered in greater detail by presenting established practical considerations for design. A pressure-saturation unit was developed in which all the compressed air supplied is dissolved into the saturator feed by continously recycling the air through a sparger, i.e. there is no air wastage. The air circulating pump operates within the pressurized circuit so that it pumps only against the hydrostatic head of water in the saturator. A vertical flow type flotation unit was developed which provides a counter current flow regime and a stable interface between the clear liquid and rising agglomerates. The accumulated agglomerates discharge freely and without mechanical assistance at the top of the unit.